In the Supreme Court of the Northwest Territories, between Le Jeune, Smith & Co. (plaintiffs), appellants, and T.B. Lafferty and A. C. Sparrow, defendants, and H.A. Sparrow (defendant), respondent [electronic resource] : amended appeal book : Smith & Watson, advocates for appellants; Lougheed, McCarthy & McCarter, advocates for respondents. - Le Jeune, Smith & Co.; Sparrow, H. A.; Sparrow, A. C.; Lafferty, T. B.; Northwest Territories. Supreme Court. ([Calgary? : s.n.], 1893)
Electronic reproduction. Mode of access: Internet. 44